Contribuição à citotaxonomia dos Scorpaeniformes (Osteichthyes - Teleostei): estudos citogenéticos em espécies do litoral do Rio de Janeiro, Brasil - Corrêa, Margaret Maria de Oliveira (1995)
The order Scorpaeniformes is morphologically diverse and the only character defining the group is a bony suborbital stay extending posteriorly from the third infraorbital to the preopercle. This order shows a great number of systematic problems and the phylogenetic relationships within the group are not clear. Four species belonging to three families of the order Scorpaeniformes were cytogenetically analyzed: Scorpaena brasiliensis, Scorpaena isthmensis (Scorpaenidae ), Prionotus punctatus (Triglidae) and Dactylopterus volitans (Dactylopteridae). The specimens were collected in the coast of Rio de Janeiro, Brazil. This study has the aim of contributing to the knowledge of the cytotaxonomy and phylogeny of the order. The karyotypes of the Scorpaenidae species analyzed in this study confirm the great chromosome diversity found in the family in previous studies. Thus far, the karyotype of P. punctatus is unique in the arder and is hypothesized to have been originated from a karyotype with high FN by several centric fissions. The karyotype of D. volitans is very similar to the other ones found in the another members of the arder Scorpaeniformes, although the phylogenetic position of Dactylopteridae remains incertain. The arder Scorpaeniformes presents a significative chromosome diversity, principally concerning the chromosomes morphology, as the result of several chromosomal rearrangements, especially pericentric inversions followed by Robertsonian translocations. This great chromosomal diversity found in a group of essentially marine fishes, differs from what is found in the majority of the other marine groups studied thus far, in which a great karyotypic stability is observed.